E-Commerce And Marketing Innovation Towards Consumer Buying Interest Case Study On Pt Ramayana Lestari Sentosa Tbk - Manap, Abdul; Idris, Nurhaifa; Zainuddin, Zainuddin; Buana, Lilik Swarnata Angga; Saepullah, Asep (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The study aims to determine the effect of e-commerce (virtual) and marketing innovation on consumer purchasing interest at PT Ramayana Lestari Sentosa Tbk. The implementation of e-commerce is carried out by PT. Ramayana Tbk in various business lines, by creating its own buying and selling website in collaboration with fintech companies such as Go-Pay and Dana. The e-commerce variable (electronic commerce) has a calculated r greater than the r table (0.183), so it can be said that all question items are able to measure what is to be measured (valid) and the e-commerce variable is 0.822, its value is greater than 0.70, so it can be said that the instrument used to measure the variable is reliable. The marketing innovation variable has a calculated r greater than the r table (0.183) and the marketing innovation variable is 0.775, its value is greater than 0.70, so it can be said that the instrument used to measure the variable is reliable. The consumer purchasing interest variable is 0.838, the value is greater than 0.70, so it can be said that the instrument used to measure this variable is reliable. Based on these results, the Sig value for the regression is 0.000 < 0.05, thus proving that e-commerce and marketing innovation simultaneously have a significant influence on consumer purchasing interest.